Micro- and nano-emulsion drug delivery systems: a review - Alzubaidy, Suhad H.; Al-Azzawi, Shafq (Pharmakeftiki, 2025)
Interest in micro- and nano-emulsions has steadily grown over recent decades, owing to their distinctive physicochemical properties and expanding utility in the medical field. These nano-scaled formulations – typically ranging from tens to several hundreds of nanometres – offer considerable potential for pharmaceutical applications. This review provides a structured overview of recent advances in micro- and nano-emulsion-based drug delivery systems. It begins by defining emulsions and their classifications, then delineates the distinctions between conventional emulsions and their micro/nano counterparts, with particular emphasis on the differences between micro- and nano-emulsions. The review further examines the principal advantages and limitations of these systems relative to other pharmaceutical formulations. Finally, it highlights their emerging roles in targeted drug delivery, underscoring their promise as versatile platforms for tissue-specific therapeutic interventions.